Qualitative and quantitative comparison of hemodynamics between MRI Measurement and CFD Simulation on Patientspecific Cerebral Aneurysm - A Review - Lim, Sheh Hong; Mohd Azrul Hisham, Mohd Adib; Mohd Shafie, Abdullah; Radhiana, Hassan (Akedemia Baru, 2020)
The significant progress in computer innovation technique, computational fluid dynamics (CFD) has been applied for real applications on patient-specific hemodynamics and extensively used to study cerebral aneurysm rupture. In addition, the computational study with representative blood vessel configuration has become a great tool in providing comprehensive information on geometry, the flow field of blood and wall shear stress (WSS). Generally, the numerical simulations have an expected problem on the specification of the exact boundary conditions which leads to unphysical numerical solutions. Therefore, this paper tends to find out whether CFD simulation manages to obtain precise and better predictions of hemodynamics patterns at present time especially for phase-contrast magnetic resonance imaging (PC-MRI) in terms of the velocity flow field and WSS distribution. Several research articles are included and their qualitative and quantitative results on hemodynamics have been compared. Both MRI measurement and CFD simulation have reasonably good agreement on velocity flow fields and a detailed spiral recirculating flow pattern can be observed in CFD simulation as compared to MRI measurement instead. However, CFD simulation has overestimated the WSS, especially at the maximum WSS location. The CFD simulation is capable to achieve good agreement on velocity flow fields with MRI measurement, yet the result for WSS distribution has to be further improved and justified with consistent assumptions and techniques.